Solving sparse principal component analysis with global support - Dey, Santanu S.; Molinaro, Marco; Wang, Guanyi (Mathematical Programming, 2023)
Row-sparse principal component analysis (rsPCA), also known as principal component analysis (PCA) with global support, is the problem of finding the top-r leading principal components such that all these principal components are linear combination of a subset of k variables. rsPCA is a popular dimension reduction tool in statistics that enhances interpretability compared to regular PCA. Methods for solving rsPCA in the literature are either greedy heuristics (in the special case of r=1) with guarantees under restrictive statistical models, or algorithms with stationary-point convergence for some regularized reformulation of rsPCA. Crucially, none of the existing computational methods can efficiently guarantee the quality of the solutions obtained by comparing against dual bounds. In this work we first propose a convex relaxation based on operator norms that provably approximates the feasible region of rsPCA within a O(logr) factor. To prove this result we use a novel random sparsification procedure that uses the Pietsch-Grothendieck factorization theorem and may be of independent interest. We also propose a simpler relaxation that is second-order cone representable and gives a (1+sqrt(r))-approximation for the feasible region. Using these relaxations we then propose a convex integer program that provides a dual bound for the optimal value of rsPCA. Moreover, it also has worst-case guarantees: it is within a multiplicative/additive factor of the original optimal value, the multiplicative factor being O(logr) or O(r)depending on the relaxation used. Finally, our experiments demonstrate both the viability of computing these dual bounds on instance with up to 2000 attributes and also their quality compared to baselines available.